Endoscope Reprocessing: Update on Controversial Issues - Choi, Hyun Ho (Clin Endosc, 2015)
Several issues concerning endoscope reprocessing remain unresolved based on currently available data. Thus, further studies are required to confirm standard practices including safe endoscope shelf life, proper frequency of replacement of some accessories including water bottles and connecting tubes, and microbiological surveillance testing of endoscopes after reprocessing. The efficacy and cost-effectiveness of newer technology that allows automated cleaning and disinfection is one such controversial issue. In addition, there are no guidelines on whether delayed reprocessing and extended soaking may harm endoscope integrity or increase the bioburden on the external or internal device surfaces. In this review, we discuss the unresolved and controversial issues regarding endoscope reprocessing.